Gemma the gymnastics fairy - Meadows, Daisy (New York : Scholastic, 2010)
While everyone in Fairyland is getting ready for the Fairy Olympics, Jack Frost's goblins steal the Sports Fairies' magic objects, and Rachel and Kristy must get back Gemma's magic hoop.
Originally published with series title The sporty fairies: London : Orchard Books, 2008.
RL: 2.
Ages 6-9.
Accelerated Reader AR
Reading Counts RC
Accelerated Reader
Keywords: Walker, Rachel (Fictitious character) -- Juvenile fiction; Tate, Kirsty (Fictitious character) -- Juvenile fiction; Fairies -- Juvenile fiction; Gymnastics -- Juvenile fiction; Olympics -- Juvenile fiction; Magic -- Juvenile fiction; Jack Frost (Legendary character) -- Juvenile fiction; Goblins -- Juvenile fiction; Fantasy fiction -- Juvenile fiction; JUVENILE FICTION -- Fantasy & Magic; JUVENILE FICTION -- Social Themes -- Friendship; Fairies; Fantasy fiction; Goblins; Gymnastics; Jack Frost (Legendary character); Magic; Olympics; Sports stories; Tate, Kirsty (Fictitious character); Walker, Rachel (Fictitious character); Fantasy fiction; Fiction; Juvenile works; Sports fiction; Fantasy fiction; Sports fiction